The Determinant Factors of Auditor Switching in The Company - Edy Suprianto; Maharani Safitri; Mufarokah Mufarokah (JURNAL ILMIAH EDUNOMIKA, 2023)
The latest rule is that the auditor must change clients after being audited three times by the same auditor. This phenomenon is something interesting to study. This study purpose is to test the factors which affect auditor switching. The population is all real estate and property industries listed on the Indonesia Stock Exchange. The results can be concluded that the variable financial distress, audit opinion and audit delay have a positive and significant effect on auditor switching. Meanwhile, the Public Accounting Firms and audit committee size variables did not prove to affect auditor switching. This result implies that the auditor must pay attention to the above factors Keywords: audit opinion, financial distress, audit delay, Public Accounting Firm size, audit committee, and auditor switching